2009
DOI: 10.1111/j.1749-4486.2009.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

Base of skull recurrences after treatment of salivary gland cancer with perineural invasion reduced by postoperative radiotherapy

Abstract: The use of postoperative radiation therapy significantly reduced the incidence of skull base recurrence among salivary gland carcinoma patients with perineural invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
(34 reference statements)
3
18
0
3
Order By: Relevance
“…The probability of skull base recurrence was 15 and 5% (p = 0.03) with and without postoperative radiation therapy, respectively. Patients with skull base recurrence had a 5-year overall survival of only 19% compared with 91% for patients without skull base recurrence [47], consistent with the findings of other authors [46,48,49]. The retrospective nature of these trials, the heterogeneity of pathologies included in many of the series of salivary gland tumors and lack of routine use of pretreatment MRI, which could have identified the presence of macroscopic PNS, are limits to the interpretation of these studies.…”
Section: Salivary Gland Cancerssupporting
confidence: 62%
See 1 more Smart Citation
“…The probability of skull base recurrence was 15 and 5% (p = 0.03) with and without postoperative radiation therapy, respectively. Patients with skull base recurrence had a 5-year overall survival of only 19% compared with 91% for patients without skull base recurrence [47], consistent with the findings of other authors [46,48,49]. The retrospective nature of these trials, the heterogeneity of pathologies included in many of the series of salivary gland tumors and lack of routine use of pretreatment MRI, which could have identified the presence of macroscopic PNS, are limits to the interpretation of these studies.…”
Section: Salivary Gland Cancerssupporting
confidence: 62%
“…Clinical target volume encompasses the GTV or site of resected tumor with an additional margin to account for subclinical spread of cancer [59][60][61]. In the report by Chen et al there was a trend for reduced recurrence for those patients in whom the skull base was included in the radiation portal, compared with those in whom it was not [47]. Other authors also concur about including the base of skull for ACC [45].…”
Section: Reviewmentioning
confidence: 95%
“…13,39 We consider electively covering the CN innervating the primary tumor site in highgrade salivary gland tumors, including ACC and SDC, and in cutaneous SCC of the face involving a named nerve. 49,52 In cases that warrant this elective neural coverage, one can consider covering additional CNs at risk secondary to anastomotic interconnections, such as those running between CNs V and VII. 53,54 These interconnections should be always covered in cases of PNTS or pathologically positive margins in immediately adjacent named nerve pathways.…”
Section: Rationale and Consensus Indications For Radiationmentioning
confidence: 99%
“…70 Accordingly, inclusion of the skull base in the irradiated volumes resulted in a trend for lower recurrence compared with treatment in which it was not included. 71 Some authors suggested that in cases with ACC involvement of a named nerve, clinical target volume should include the course of the nerve back to the skull base. 16,62 Inclusion of the brainstem should possibly be required in the presence of macroscopic disease or positive surgical margins in the skull base and neural foramens.…”
Section: Perineural Spread and Treatment Considerationsmentioning
confidence: 99%